Artisanal fishing characterization and spatio-temporal occurrence of marine shrimp (Crustacea, Decapoda, Penaeidae) in the littoral of Lucena, Paraíba, Brazil - Nascimento, Glória Cristina Cornélio do; Costa, Dimitri de Araújo; Sá, Raquel Ferreira de; Christoffersen, Martin Lindsey; Crispim, Maria Cristina Basilio (Ciência e Natura, 2018)
The present study distinguishes types of fishing activities. It records the most economically exploited shrimps in the municipality of Lucena, Paraíba, Xiphopenaeus kroyeri (“espigudo”), and Penaeus schmitti (white shrimp). From October 2014 to October 2015, samples containing 700 gr of shrimp were collected at three sites of artisanal fishing. Data on temperature, ammonium, nitrate, nitrite, chlorophyll-a, salinity, pH, and dissolved oxygen were recorded. Two different shrimp species are commercially used in the region, of 2,628 sampled individuals, X. kroyeri predominated, with 1,957 individuals, followed by P. schmitti, with 671 individuals. At localities 1 (in Lucena beach) and 2 (Fagundes beach) both species were present, the X. kroyeri being predominant, but at locality 3 (Costinha beach) only the P. schmitti was recorded. The regional wet season influenced salinity during the months of the year, producing positive or negative correlations among species found at each locality depending on what was analysed. It is relevant to understand the relationship between fishing resources and environmental variables which provide information about fishing dynamics and permits the development of strategies for the maintenance of stocks and fishing areas, as well as permitting the establishment of public regulations for the better preservation and conservation of marine areas and estuaries on which many species depend for the completion of their life cycles.